Radioiodine Ablation in Postpartum Patient with Differentiated Thyroid Cancer: A Case Report and Review of Literature. - Ahmad Zaid Zanial; H Fadzilah; A K M Ali (Asian Journal of Medicine & Health Sciences, 2024)
Well differentiated thyroid carcinoma is the most commonly seen thyroid cancer. One of the presenting symptoms is thyroid nodule. In most cases following initial workup and whereby tumour is resectable, surgery is the mainstay of treatment. The subsequent postsurgical management utilising radionuclide Iodine-131 (I-131) has long been established and extensively being studied and discussed. This present case report illustrates the general overview of differentiated thyroid cancer (DTC) as well as the concerns related to radioiodine ablation in a postpartum patient with DTC.